2019
DOI: 10.5114/ceji.2019.92803
|View full text |Cite
|
Sign up to set email alerts
|

Etanercept in the treatment of Graves’ ophthalmopathy with primary hypothyroidism and rheumatoid arthritis

Abstract: Graves' ophthalmopathy (GO) is an autoimmune disease affecting ocular and orbital tissues. Overproduction of tumor necrosis factor α (TNF-α) in rheumatoid arthritis (RA) and GO has destructive consequences. The subject of this paper is a case of a female patient initially diagnosed with primary hypothyroidism substitution with levothyroxine, and subsequent diagnosis of RA with insufficient therapeutic efficacy of a standard medication. Three years later, the patient presented symptoms and signs of GO. Etanerce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…OF have an increased expression of TSH-R, and a strong upregulation of TNF-a and IL-6, in the pathogenesis of GO (88).…”
Section: Drugs Targeting Cytokines In Gd and Gomentioning
confidence: 99%
See 1 more Smart Citation
“…OF have an increased expression of TSH-R, and a strong upregulation of TNF-a and IL-6, in the pathogenesis of GO (88).…”
Section: Drugs Targeting Cytokines In Gd and Gomentioning
confidence: 99%
“…After 3 years, she showed symptoms and signs of GO. Then, the patient received etanercept for RA, and after 4 months, the ocular symptoms ameliorated and exophthalmos decreased, showing that RA and GO can share similar pathogenic characteristics (88).…”
Section: Drugs Targeting Cytokines In Gd and Gomentioning
confidence: 99%
“…Another paper reported a case of a patient with RA and GO. She was treated with etanercept for RA achieving also a clinical improvement of GO symptoms (Boskovic et al, 2019). Additional researches are needed in order to evaluate the effectiveness of TNF-α inhibitors, and to compare its side effects with the current medical treatment.…”
Section: Etanercept and Tocilizumabmentioning
confidence: 99%
“…Summary of Clinical Trials and Therapeutic Applications. The efficacy of selected anti-TNFα agents in GO was described in several case reports [56][57][58]. A prospective nonrandomized trial reported the use of etanercept (25 mg twice weekly for 12 weeks) in 10 patients with active GO [59].…”
Section: Anti-tumor Necrosis Factor Alpha Therapymentioning
confidence: 99%